Socioeconomic differences in childhood vaccination in developed countries: a systematic review of quantitative studies. (2nd November 2017) - Bocquier, Aurélie; Ward, Jeremy; Raude, Jocelyn; Peretti-Watel, Patrick; Verger, Pierre
ABSTRACT: Introduction : The reasons for vaccine hesitancy and its relation to individual socioeconomic status (SES) must be better understood. Areas covered : This review focused on developed countries with programs addressing major financial barriers to vaccination access. We systematically reviewed differences by SES in uptake of publicly funded childhood vaccines and in cognitive determinants (beliefs, attitudes) of parental decisions about vaccinating their children. Using the PRISMA statement to guide this review, we searched three electronic databases from January 2000 through April 2016. We retained 43 articles; 34 analyzed SES differences in childhood vaccine uptake, 7 examined differences in its cognitive determinants, and 2 both outcomes. Expert commentary : Results suggest that barriers to vaccination access persist among low-SES children in several settings. Vaccination programs could be improved to provide all mandatory and recommended vaccines 100% free of charge, in both public organizations and private practices, and to reimburse vaccine administration. Multicomponent interventions adapted to the context could also be effective in reducing these inequalities. For specific vaccines (notably for measles, mumps, and rubella), in UK and Germany, uptake was lowest among the most affluent. Interventions carefully tailored to respond to specific concerns of vaccine-hesitant parents, without reinforcing hesitancy, are needed.